Molecular validation of the specific status of Parablennius sanguinolentus and Parablennius parvicornis (Pisces: Blenniidae) - Almada, Frederico José Oliveira de (2012)
Parablennius sanguinolentus and P. parvicornis have been classified as either two distinct species or as two sub-species depending on the different criteria used to classify them. An analysis of fragments of mitochondrial 12S and 16S rDNA showed that the genetic distance between samples of P. sanguinolentus and P. parvicornis is similar or higher than those found for other blenniids that are widely recognized as distinct species. These results, together with the distinct geographical distributions and meristic differences, support the conclusion that P. sanguinolentus and P. parvicornis should be considered as two different species.